Women's Studies in Focus: Infusing Feminism: A Discussion of Methodology, Pedagogy, and Praxis - van der Meulen, Emily; Friedman, May; Hallett, Vicki S.; Gibaldi, Diana; Carter, Claire (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This paper explores the continuum of feminist research to feminist teaching by looking at pedagogy, inquiry, and practice. It presents perspectives on feminist life writing, research and action research, as well as queer positive and experiential classrooms. The authors provoke a critical conversation about feminist methodology, pedagogy and praxis.